(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper provides an in-depth analysis of issues concerning the human person and its eschatology in Urhobo ontology, with specific interest in how the Urhobo people of Southern Nigeria conceive and understand the concepts of existence, death, and destiny. The study addresses the perceived neglect of holistic African perceptions in the analysis of the human person, particularly in relation to the concepts of personhood and the afterlife. The essence of this study is to highlight traditional African beliefs that provide a moral and communal framework shaping scholarly discussions as they relate to life and death. In Urhobo thought, personhood is conceived as a unity of body, spirit, and destiny. The study also highlights how their eschatological beliefs provide a moral and communal framework that shapes both life and death. Employing the methods of philosophical analysis and hermeneutics, the paper argues that the Urhobo view death not as an end but as a transition into Erivwin, the spiritual realm, and that moral conduct, communal belonging, and proper burial rites determine one’s ultimate destiny. Ancestorhood is considered the highest fulfillment and attainment of the human person, serving as both a moral ideal and an eschatological goal. The paper concludes by affirming that Urhobo ontology offers a holistic perception of the human person, where morality, communal living, and destiny are inseparable, contributing importantly to global philosophical reflections on the themes of life and the afterlife.